3D cell culture alters signal transduction and drug response in head and neck squamous cell carcinoma - Heid, Jonas; Affolter, Annette; Jakob, Yvonne; Kern, Johann; Rotter, Nicole; Tenschert, Esther; Lammert, Anne (Oncology letters, 2022)
Epidermal growth factor receptor (EGFR) upregulation is a typical characteristic of head and neck squamous cell carcinoma (HNSCC). However, tyrosine kinase inhibitors have not yet been able to achieve enough therapeutic benefit in clinical trials to justify their use in standard therapy regimens. At present, little is known about the reasons for this treatment failure. In the present study, the HNSCC cell lines UM‑SCC‑11B and UM‑SCC‑22B were tested for their response to tyrosine kinase inhibitors (TKI) under 2D and 3D cell culture conditions. Absorption and luciferase‑based viability assays were used for this, as well as optical evaluation via fluorescence microscopy. In addition, EGFR and HER3 expression as well as the downstream signalling pathways PI3K/AKT/mTOR and RAS/RAF/MEK/ERK were investigated using western blotting. Cell line UM‑SCC‑11B revealed a strong resistance to lapatinib under 3D cell culture conditions, while a good response to TKI therapy was observed under 2D cell culture conditions. An associated overexpression of phosphorylated HER3 under 3D cell culture conditions offered a plausible explanation for the altered treatment response. The results of the present study represent an idea of how signalling mechanisms of cancer cells can be changed using different cell culture methods. Overall, 3D cell culture could be an important component in the analysis of resistance mechanisms in cancer therapy.
Gesehen am 16.01.2024